E-101 Postoperative ischemic events in patients undergoing carotid artery stenting using algorithmic selection of emboli protection. (22nd July 2018) - Kawabata, Y; Nakajima, N; Miyake, H; Fukuda, S; Tsukahara, T
Abstract : Objective: To determine the safety and effectiveness of emboli protection during carotid artery stenting (CAS). Methods: The clinical outcomes of 59 patients who underwent CAS with emboli protection devices were reviewed. Patients who underwent CAS associated with thrombectomy and who had preoperative mRS >3 were excluded from the study. 46 patients were male, and 13 were female. The median age was 72.5 years (range 59–89), and 44 lesions were asymptomatic. Emboli protection device was selected based on the presence of symptom, carotid wall MRI, and lesion length. The combined 30 day complication rates (transient ischemic attack, minor stroke, major stroke, or death) were analyzed. Results: Filter-type emboli protection device was selected in 23 procedures, distal balloon protection in 16 procedures, and proximal occlusive protection in 21 procedures. Our patients (6.8%) experienced a transient ischemic attack, and one patient (1.7%) had a minor stroke within 30 days of the procedure. No patients experienced procedure-related morbidities (mRS >2) or deaths. Conclusions: Our data suggest that algorithmic selection of emboli protection based on the presence of symptom, carotid wall MRI, and lesion length can be effective in the prevention of major ischemic adverse events. Disclosures: Y. Kawabata: None. N. Nakajima: None. H. Miyake: None. S. Fukuda: None. T. Tsukahara: None.